High performance polyethylene nanocomposite fibers - A. Dorigato; M. D'Amato; L. Fambri; A. Pegoretti (eXPRESS Polymer Letters, 2012)
A high density polyethylene (HDPE) matrix was melt compounded with 2 vol% of dimethyldichlorosilane treated fumed silica nanoparticles. Nanocomposite fibers were prepared by melt spinning through a co-rotating twin screw extruder and drawing at 125°C in air. Thermo-mechanical and morphological properties of the resulting fibers were then investigated. The introduction of nanosilica improved the drawability of the fibers, allowing the achievement of higher draw ratios with respect to the neat matrix. The elastic modulus and creep stability of the fibers were remarkably improved upon nanofiller addition, with a retention of the pristine tensile properties at break. Transmission electronic microscope (TEM) images evidenced that the original morphology of the silica aggregates was disrupted by the applied drawing.